Design and Preparation Methods of Metallic/Ceramic Barrier Layer for Titanium - Fire Retardant - LI Jia - hui, LIU Mei - jun (Cailiao Baohu)
The metallic/ceramic barrier layer could be used not only for the titanium - fire retardant abradable seal coatings to play the role of fire - retardant, but also as the thermal barrier coatings for hot - section components in aero - engines. In this paper, based on the application of titanium - fire retardant coatings for aero - engine compressor, the structure design, coating materials and preparation methods of metallic/ceramic barrier layer system were systematically reviewed. For the coating materials, the material composition design, property characteristies and synthesis methods were introduced, respectively. In terms of coating preparation technique, three methods including plasma spraying (PS), electron beam physical vapor deposition (EB - PVD) and new plasma spray physical vapor deposition (PS - PVD) were described. Finally, aiming at the development requirements of titanium - fire retardant coatings, the future development directions of metallic/ceramic barrier layer were proposed, including material upgrading, process optimization, performance characterization and coating technology theory system.